Car Wash Ordering App for Better Queue - Eko Setyo Purwanto; Mohamad Gandi Efendi; Raditya Tohpati; Patrick Marionatha (Bina Nusantara University, 2022)
This study aims to create a booking application that is applied in a car wash. Seeing the very rapid development of technology, one of which is the booking application There are so many business people who take advantage of this booking application, for example, hotel booking applications, ticket bookings, etc. But there is some business that has not taken advantage of this booking application, one of which is the car wash business. Most car wash businesses still use manual methods in the process, from recording customer data and payments. In using this manual method, many problems occur. for example, recording incorrect data, counterfeiting money, etc. Therefore, a study was conducted using the system development method, namely Waterfall. The waterfall method includes Analysis, Design, Coding, and Testing. The results obtained from this study are a Car Wash booking application by utilizing the IoT topic which is expected to help problems that occur in the car wash business.